2002
DOI: 10.1002/hec.693
|View full text |Cite
|
Sign up to set email alerts
|

Superbugs II: how should economic evaluation be conducted for interventions which aim to contain antimicrobial resistance?

Abstract: To date, there has been little examination of the problems associated with conducting economic evaluation for interventions designed to contain antimicrobial resistance. There are two quite different types of intervention aimed at containing antimicrobial resistance: interventions which are designed to avoid the emergence of resistant organisms; and interventions that are designed to avoid the transmission of resistance organisms. Four aspects of economic evaluation where the ease of assessment might be expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 40 publications
0
40
0
1
Order By: Relevance
“…As a result, antibiotic resistance increases the economic burden for both patient and the society. 4,5 This was confirmed by a study that showed an association of 29.3% higher total hospital cost for each admission and a 23.8% increase in the length of stay among patients infected with hospitalacquired infection (HAI) caused by a resistant Gramnegative bacteria compared to those with HAIs caused by nonresistant pathogens. 6 In addition the most common used antibiotics namely ß-lactam antibiotics, fluoroquinolones, glycopeptides, antitubercular drugs, imidazoles, and other antimicrobials have been shown to contribute toward nearly 48.7% of all the reported adverse drug reactions (ADRs).…”
Section: Introductionmentioning
confidence: 91%
“…As a result, antibiotic resistance increases the economic burden for both patient and the society. 4,5 This was confirmed by a study that showed an association of 29.3% higher total hospital cost for each admission and a 23.8% increase in the length of stay among patients infected with hospitalacquired infection (HAI) caused by a resistant Gramnegative bacteria compared to those with HAIs caused by nonresistant pathogens. 6 In addition the most common used antibiotics namely ß-lactam antibiotics, fluoroquinolones, glycopeptides, antitubercular drugs, imidazoles, and other antimicrobials have been shown to contribute toward nearly 48.7% of all the reported adverse drug reactions (ADRs).…”
Section: Introductionmentioning
confidence: 91%
“…And resistant infections are harder to treat [5]. In one study, Coast has articulated the difficulty of estimating the aggregate, long-term harm to the population because of diffuse nature of the effects, comparison of current and future benefits and harms, uncertainty about the future course of resistance, and the possible development of new antibacterial agents, among other reasons [6]. Thus, the harm of any individual course of antibiotic (appropriate or not) is unknown, but small.…”
Section: Commentarymentioning
confidence: 99%
“…Prices are allowed to vary with resistance levels because antibiotic manufacturers with market power may increase prices if close substitutes are less effective due to resistance. Equation (6) can be rewritten to separate resistance-attributable costs into two components:…”
Section: The Modelmentioning
confidence: 99%